The effect of asymmetrical relationship of oil price shocks on gross domestic product - Zalina Zainal; Mukhriz Izraf Azman Aziz; Mohd Faisol Md. Salleh (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper revisits the asymmetrical crude oil prices and Gross Domestic Product (GDP) relationship for Malaysia and Indonesia using Hansen (2000) Threshold regression method. The empirical analysis uses quarterly data for the period of 1990 (quarter 1) until 2018 (quarter 1). The paper confirms the nonlinearities in the oil price-GDP relationship for Malaysia and Indonesia. The findings reveal that when oil prices are below USD37, oil price shocks have a negative impact on Malaysian GDP, but positively affect GDP when oil price are between USD37 to USD55. Indonesia’s GDP, on the other hand, responds favourably to changes in oil prices when they are below USD47, but negatively affects GDP when oil price exceeds USD47. Both countries’ GDP responses to oil price shocks are linked to the issues such as the degree of oil dependency, oil self-sufficiency, and government efficiency in managing revenue from the oil sector and the ease with which critical policy adjustments take place.